2022
DOI: 10.1039/d1cc06507f
|View full text |Cite
|
Sign up to set email alerts
|

Selective benzylic Csp3–H bond activations mediated by a phosphorus–nitrogen PN3P-nickel complex

Abstract: In contrast to the typical Csp2−H activation, a PN3P-Nickel complex chemoselectively cleaved the benzylic Csp3–H bond of toluene in the presence of KHMDS, presumably via an in situ generated potassium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Research in our group is predominantly concerned with the exploration of metal–ligand cooperative reactivity by utilizing a series of phosphorus–nitrogen PN 3 (P)-pincer complexes through aromatization/de-aromatization of the central pyridine ring. , Recently, we have further demonstrated that modification of the PN 3 P-pincer systems using a ligand postmodification strategy can afford a series of new metal pincer complexes with some unprecedented reactivities. For example, photoactivation of the corresponding azide complex in the presence of RNC resulted in the incomplete transfer of nitrogen atoms to isocyanides to produce the monocarbodiimide complexes . Herein, we further demonstrate the room-temperature photoactivation of CO 2 and CS 2 by the proposed nickel nitridyl or phosphiniminato intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Research in our group is predominantly concerned with the exploration of metal–ligand cooperative reactivity by utilizing a series of phosphorus–nitrogen PN 3 (P)-pincer complexes through aromatization/de-aromatization of the central pyridine ring. , Recently, we have further demonstrated that modification of the PN 3 P-pincer systems using a ligand postmodification strategy can afford a series of new metal pincer complexes with some unprecedented reactivities. For example, photoactivation of the corresponding azide complex in the presence of RNC resulted in the incomplete transfer of nitrogen atoms to isocyanides to produce the monocarbodiimide complexes . Herein, we further demonstrate the room-temperature photoactivation of CO 2 and CS 2 by the proposed nickel nitridyl or phosphiniminato intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a series of noble metal catalysts demonstrated remarkable efficiency for the carbene and nitrene transfer reactions. , In sharp contrast, whereas the base-metal complexes are excellent catalyst candidates, they have not been explored much for these C–H bond amination reactions, though they may possibly be ideal catalyst candidates compared to the noble metal complexes. While significant developments have been achieved for the catalytic C–H amination reactions employing azides, N -oxy reagents, , and iminoiodinanes as the nitrene sources, the use of 1,2,3,4-tetrazole remains almost rare, although it could potentially be beneficial owing to its additional 2-pyridyl handle for finding new properties related to drug discovery and medicinal chemistry.…”
mentioning
confidence: 99%